Theoretical approaches to defining the middle class and foreign experience of its formation - Kurbet O. P. (Український соціум)
This paper is devoted to reveal how the concept of the middle class evolved and the peculiarities of its formation abroad at the stage of acquiring mass character. Author reviewes mentions of the middle class, along with the descriptions of its role in society and the state system, are presented in the works of different thinkers. Starting from Aristotle, who singled out the tertiary group of citizens as the basis of democracy; M. Weber, who took into account the criterion of education, qualifications, and skills; T. Veblen, who paid attention to the criterion of consumption to later developments, which consider the criterion of access to high technologies, knowledge and entrepreneurial activity. The paper determines that for a long time, the middle class was considered in the context of the developed countries of its time. It is underlined, that depending on the historical era, it was Rome, Greece, Germany, and the USA. Only in recent decades has there been a trend of increasing interest in the middle class of developing countries, expanding the subject field of middle-class studies in the context of economic inequality due to the involvement of other factors such as racial and gender characteristics. The paper reveals that at various historical stages, the main factors in the formation of the middle class were urbanization and trade, the development of world trade and colonialism, industrial revolutions, enlightenment and the spread of liberal ideals, labor movements and social reforms, development and mass education. Author shows that the second half of the 20th century was a period of mass middle class formation, closely interconnected with postwar recovery after WWII and the formation of welfare states. In particular, one of the most essential factors in the rapid growth of the American middle class, the so-called golden years (1947–1973), was the targeted government policies and social programs of both the postwar period and earlier. Modern welfare states’ crucial role in shaping the middle class, reducing economic inequality, and mitigating the effects of economic crises, is described. This experience has practical value for the formation of the Ukrainian middle class, which is facing significant challenges exacerbated by the ongoing war. The historical context of middle class formation in post-socialist countries has been marked by a lack of political decisions similar to those in the West. This highlights the need for further scientific research on the topic.